Implications of Limited Liability Company After Being Declared Bankrupt - Lia Salsiah (Ridwan Institute, 2023)
Bankruptcy is a situation where a debtor is unable to pay his debts and can be billed. Companies that have been declared bankrupt in this case must be dissolved in order to change their legal entity status so as not to cause losses to related parties. A limited liability company that is declared bankrupt does not immediately stop and disband but still exists as a legal entity. Under certain circumstances, it continues to operate as usual, the limited liability company does not go bankrupt and can still carry out its business activities. This study formulates two problems, namely first, what is the process for dissolving a Limited Liability Company after being declared bankrupt? and second, what are the implications of a Limited Liability Company after being declared bankrupt. The type of research used in this case is normative juridical. Legal research conducted by reviewing the literature is referred to as secondary data. The results of this study are that liquidation is processed by first holding a General Meeting of Shareholders and the implication is that a Limited Liability Company after being declared bankrupt makes the company lose its right to manage and control the company's assets.